JASLAR MIYNETI HÁM OLARDÍ HUQÍQÍY QORǴAW - Ismailova, Z. (ILIM hám JÁMIYET, 2018)
The policy concerning the youth is a priority direction of the state activity of the Republic of Uzbekistan. Article 37 of the Constitution of the Republic of Uzbekistan guarantees the possibilities of creation of working conditions for employecs. Labour protection of the youth means providing safety of the youth in labour process, preservation of their health and ability to work.